Web based road accident analysis / Rosniza Mujar - Mujar, Rosniza (1999)
Web based Road Accident Analysis is a broadcasting statistical information on Notes users and Internet users, it works as a tool for police traffic in Shah Alam to collect accident data and provide latest information for all notes users especially and internet users.